The Routledge Companion to Art and Activism in the Twenty-First Century (Taylor & Francis, 2023)
The Routledge Companion to Art and Activism in the Twenty-First Century brings together a wide range of geographical, cultural, historical, and conceptual perspectives in a single volume of new essays that facilitate a deeper understanding of the field of art activism as it stands today and as it looks towards the future. The book is a resource for multiple fields, including art activism, socially engaged art, and contemporary art, that represents the depth and breadth of contemporary activist art worldwide. Contributors highlight the predominant lines of enquiry within the field, uncover challenges faced by scholars and practitioners of activist art, and facilitate dialogue that might lead to new directions for research and practice. The editors hope that the volume will incite further conversation and collaboration among the various participants, practitioners, and researchers in the growing field of art activism. The audience includes scholars and professors of modern and contemporary art, students in both graduate and upper-level undergraduate programs, as well as artists, curators, and museum professionals. Each essay can stand on its own, making the companion a flexible resource for students and educators working in art history, museum studies, community practice/socially-engaged art, political science, sociology, and ethnic and cultural studies.
English
Keywords: History of art / art & design styles; The arts: general issues; activism, Africa, apartheid, dissent, Haroon Gunn-Salie, homophobia, neo-liberal, resistance, Section27, sexual violence, , South Africa, Tokolos Stencils Collective, visual activism, Zanele Muholi, artists, art history, injustice, social justice, inequality